Gospoda-tovarishchi . Gospoda-tovarishchi . Gentlemen-Comrades . Господа-товарищи - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. KGB activity undermining patriotic movements; Cuban Social-Democratic Center representatives visit Moscow. Featured in the program: Korolev, Stanislav (Retired KGB Colonel); Sterligov, Aleksandr Nikolaevich (Retired KGB General) Деятельность КГБ по подрыву патриотических движений; приезд представителей социал-демократического центра Кубы в Москву. В программе участвуют: Королев, Станислав (Полковник КГБ в отставке); Стерлигов, Александр Николаевич (Генерал КГБ в отставке)